The translational regulator FMRP controls lipid and glucose metabolism in mice and humans - Antoine Leboucher; Didier F. Pisani; Laura Martinez-Gili; Julien Chilloux; Patricia Bermudez-Martin; Anke Van Dijck; Tariq Ganief; Boris Macek; Jérôme A.J. Becker; Julie Le Merrer; R. Frank Kooy; Ez-Zoubir Amri; et al. (Molecular Metabolism, 2019)
Objectives: The Fragile X Mental Retardation Protein (FMRP) is a widely expressed RNA-binding protein involved in translation regulation. Since the absence of FMRP leads to Fragile X Syndrome (FXS) and autism, FMRP has been extensively studied in brain. The functions of FMRP in peripheral organs and on metabolic homeostasis remain elusive; therefore, we sought to investigate the systemic consequences of its absence. Methods: Using metabolomics, in vivo metabolic phenotyping of the Fmr1-KO FXS mouse model and in vitro approaches, we show that the absence of FMRP induced a metabolic shift towards enhanced glucose tolerance and insulin sensitivity, reduced adiposity, and increased β-adrenergic-driven lipolysis and lipid utilization. Results: Combining proteomics and cellular assays, we highlight that FMRP loss increased hepatic protein synthesis and impacted pathways notably linked to lipid metabolism. Mapping metabolomic and proteomic phenotypes onto a signaling and metabolic network, we predicted that the coordinated metabolic response to FMRP loss was mediated by dysregulation in the abundances of specific hepatic proteins. We experimentally validated these predictions, demonstrating that the translational regulator FMRP associates with a subset of mRNAs involved in lipid metabolism. Finally, we highlight that FXS patients mirror metabolic variations observed in Fmr1-KO mice with reduced circulating glucose and insulin and increased free fatty acids. Conclusions: Loss of FMRP results in a widespread coordinated systemic response that notably involves upregulation of protein translation in the liver, increased utilization of lipids, and significant changes in metabolic homeostasis. Our study unravels metabolic phenotypes in FXS and further supports the importance of translational regulation in the homeostatic control of systemic metabolism. Keywords: Fragile X mental retardation protein, RNA-binding protein, Translation, Metabolism, Glucose, Lipids